Climate change and maple syrup: Producer observations, perceptions, knowledge, and adaptation strategies - Ahmed, Selena; Lutz, David; Rapp, Joshua; Huish, Ryan; Dufour, Boris; Brunelle, Autumn; Morelli, Toni Lyn; Stinson, Kristina; Warne, Teresa (Frontiers in Forests and Global Change, 2023)
Introduction Climate change is impacting forest-based agricultural systems with implications for producer decision-making and livelihoods. This article presents a case study on the observations, perceptions, knowledge, and adaptation strategies of maple syrup producers in the United States to climate change. Methods We carried out two semi-structured surveys with maple producers on: (1) climate change and its impacts on the maple system (n = 106 participants); and (2) responses to climate adaptation scenarios (n = 98 participants). Additionally, we carried out two focus groups and key informant interviews (n = 70+) to understand barriers and opportunities for climate adaptation. One of these focus groups and follow up key informant interviews was with tribally affiliated community members with the intention to acknowledge Indigenous Peoples’ voices, history, and relationships to the land. Results Findings highlight that most of the surveyed producers (89%) have experienced the negative impacts of climate on maple syrup production. While 40% of participants feel concerned regarding the future of the maple system, 39% feel hopeful, with significant differences based on the age of the surveyed producers. The majority of producers have adapted their harvesting practices to climate effects. Producers shared knowledge of multiple adaptation strategies in response to climate scenarios comprised of: (1) stand management practices such as diversification of sap species tapped; (2) harvesting practices such as changing the type and number of taps; (3) sap processing practices focused on the integration of technology such as the use of an evaporator and reverse osmosis; and (4) marketing practices such as innovation of products and marketing different maple syrup characteristics. Responses shared by tribally affiliated producers highlight knowledge of multiple adaptation strategies that focus on long-term ecological management of forests rather than technological solutions. Discussion Overall, findings emphasize the importance of cooperation and diversification at every level and dimension of the maple system for its long-term resilience.